WHAT IS A TEACHER: HISTORY AND MODERNITY - Kim, N.P.; Shumeiko, T.S. (Publisher of Kostanay State Pedagogical Institute, 2018)
The article deals with the role of the teacher at the society in historical and modern aspects, features of teacher’s personality and his activity.
Keywords: teacher; the role of the teacher’s personality; features of teacher’s personality and activity